Removal of chromium (Cr) and copper (Cu) from domestic wastewater using chitosan flakes from seafood waste - Fauzi, Baharudin; Muhammad Akmal, Najman; Irma Noorazurah, Mohamad; Zaizatul Zafflina, Mohd Zaki; Muhd Norhasri, M. S.; Suriati, Ghazali (Thai Society of Higher Eduation Institutes on Environment, 2025)
Heavy metals in wastewater from various sources pose significant risks to ecosystems and human health. This study investigates the effectiveness of chitosan, a biopolymer derived from seafood waste, in removing chromium (Cr) and copper (Cu) from domestic wastewater. The adsorption efficiency of chitosan was evaluated based on adsorbent dosage and contact time. Chitosan was synthesized through demineralization, deproteination, and deacetylation of seafood waste. Adsorption experiments were conducted using chitosan dosages of 2 g, 4 g, and 6 g, with contact times of 5, 30, and 60 minutes. The results indicate that increasing the adsorbent dosage enhances the removal efficiency of both Cr and Cu ions. Specifically, Cr removal improved from 34.73% at 2 g to 56.25% at 4 g and further to 78.40% at 6 g. Similarly, Cu removal efficiency increased from 28.21% at 2 g to 56.41% at 4 g and reached 82.05% at 6 g. Additionally, prolonged contact time significantly enhanced metal ion removal. Cr removal increased from 18.06% after 5 minutes to 50.00% after 30 minutes and 72.92% after 60 minutes. A similar trend was observed for Cu, with removal efficiency rising from 17.95% at 5 minutes to 55.13% at 30 minutes and 75.64% at 60 minutes. These findings suggest that extended contact time provides greater opportunities for adsorption, improving the removal efficiencies of Cr and Cu ions. Overall, this study demonstrates that chitosan is an effective adsorbent for Cr and Cu removal from wastewater, with adsorption efficiency influenced by both adsorbent dosage and contact time.